Contribuições da psicanálise de Freud e Lacan a uma Psicotherapia outra: a clínica do sujeito na saúde coletiva - Périco, Waldir [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Our main objective was to reflect on the clinic of Psychosocial Care in the light of technical-theoretical as well as ethical-political psychoanalytic and Marxian references, considering the paradigmatic analysis, postulated by Costa-Rosa, who defines the Psychosocial Paradigm as a step beyond the Brazilian Psychiatric Reform. From a clinical and institutional praxis, we have attempted to found a modality of psicotherapy in which Freud and Lacan’s psychoanalysis is applied. We specify the focus of this reflection in the field of Collective Health and in the clinic of suppression (context of “neurosis”). We start from the Intercessor Device as a new Mode of Production of subjectivity and “knowledge”. Of transdisciplinary nature, the Intercessor Device originates mainly from psychoanalysis and Historical Materialism - as well as from inspirations of the french Institutional Analysis and Philosophy of Difference - to define two radically different moments of production: that of clinical praxis together with the “subjects of treatment” and of institutional praxis with the “collective of work”; and the moment of theoretical reflection, produced a posteriori, on the production process carried out along the first moment. If Freud envisioned the possibility of inclusion of psychoanalysis in public institutions, our reflections intend to demonstrate that this endeavor is both possible and ethically necessary. For such, we also resort to theoretical-technical and ethical unfoldings also carried out by Lacan. In this perspective, we consider that if psychotherapies in general, from an active “healer”, produce grafts of imaginary-tautological sense in trying to suture the slit opened up by anxiety, producing readaptation in favor of the socially-instituted, anOther psychotherapy sets itself out from the psychoanalytic ethical guidance of suspending Knowledge-Power-cure, having as effect the ...

Nosso objetivo principal foi pensar a clínica da Atenção Psicossocial à luz dos referenciais teórico-técnicos e ético-políticos psicanalítico e marxiano, considerando a análise paradigmática, postulada por Costa-Rosa, que define o Paradigma Psicossocial como um passo além da Reforma Psiquiátrica brasileira. A partir da práxis clínica e institucional, tentamos fundamentar uma modalidade de psicotherapia na qual a psicanálise do campo de Freud e Lacan é aplicada. Especificamos o enfoque desta reflexão no campo da Saúde Coletiva e na clínica do recalcamento (contexto das “neuroses”). Partimos do Dispositivo Intercessor, como um novo Modo de Produção de subjetividade e “conhecimento”. De natureza transdisciplinar, o Dispositivo Intercessor parte, principalmente, da psicanálise e do Materialismo Histórico – bem como de inspirações da Análise Institucional francesa e da Filosofia da Diferença – para definir dois momentos de produção radicalmente diferentes: o momento da práxis clínica junto aos “sujeitos do tratamento” e da práxis institucional junto ao “coletivo de trabalho”; e o momento da reflexão teórica, produzida a posteriori, sobre o processo de produção realizado no primeiro momento. Se Freud idealizou a possibilidade de inserção da psicanálise nas instituições públicas, nossas reflexões pretendem demonstrar que essa empreitada é tão possível quanto eticamente necessária. Para tal, recorremos também aos desdobramentos teórico-técnicos e éticos realizados por Lacan. Nessa perspectiva, consideramos que, se as psicoterapias em geral, partindo de “um cura” ativo, fazem enxertos de sentido imaginário-tautológico na tentativa de suturar a fenda aberta pela angústia, produzindo readaptação a favor do instituído social, uma psicotherapia Outra parte da orientação ética psicanalítica de suspensão do Saber-Poder-curar, tendo como ...
Keywords: Freud, Sigmund, 1856-1939; Lacan, Jacques 1901-1981; Psicanalise; Materialismo historico; Psicoterapia; Saúde pública; Psycotherapy in Collective Health